MEMBANGUN LEMBAGA DAKWAH YANG INNOVATIF DI ERA DISRUPTIF - Lulu Firdauz Ramadhani; Cecep Castrawijaya (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The development of innovative da'wah institutions is increasingly important in addressing the dynamics of social change in the disruptive era. This study aims to explore innovative strategies within da'wah institutions, focusing on clear vision and mission, the utilization of digital technology, and da'wah methods that are responsive to cultural diversity. In the context of Indonesia, which is rich in religious, cultural, and linguistic diversity, da'wah institutions face the challenge of avoiding conflict and fostering social harmony. The research method employed is descriptive qualitative through literature study, encompassing the analysis of literature from primary and secondary sources. The data collected are analyzed to identify key elements that support the effectiveness of da'wah. The results indicate that a strong vision serves as a driver for innovation, while digital technology facilitates broader message dissemination. Additionally, multicultural approaches and creative content have proven effective in reaching diverse audiences. These findings provide guidelines for da'wah institutions to enhance their relevance and effectiveness in spreading religious values within a complex society.